Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijerph20020913
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diagnosis, Prognosis and Immune Infiltration Response to the Expression of the Ferroptosis-Related Molecule HAMP in Clear Cell Renal Cell Carcinoma

Abstract: Background. Hepcidin antimicrobial peptide (HAMP) is a key factor in maintaining iron metabolism, which may induce ferroptosis when upregulated. However, its prognostic value and relation to immune infiltrating cells remains unclear. Methods. This study analyzed the expression levels of HAMP in the Oncomine, Timer and Ualcan databases, and examined its prognostic potential in KIRC with R programming. The Timer and GEPIA databases were used to estimate the correlations between HAMP and immune infiltration and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The immune function of macrophages is influenced by their ability to regulate cellular iron homeostasis [ 47 ], and M1 macrophages have a high ferritin content and are susceptible to iron deposition [ 48 ]. The hepcidin level is related to the immune infiltration level of macrophages, positively correlating with the M1 type and negatively correlating with the M2 type [ 49 ]. A study demonstrated that activated hepcidin led to iron overload in macrophages within plaques, resulting in cellular cholesterol imbalance and the formation of foam cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immune function of macrophages is influenced by their ability to regulate cellular iron homeostasis [ 47 ], and M1 macrophages have a high ferritin content and are susceptible to iron deposition [ 48 ]. The hepcidin level is related to the immune infiltration level of macrophages, positively correlating with the M1 type and negatively correlating with the M2 type [ 49 ]. A study demonstrated that activated hepcidin led to iron overload in macrophages within plaques, resulting in cellular cholesterol imbalance and the formation of foam cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though surgical resection remains the primary method of therapy for restricted KIRC, some patients could still have distant metastases after surgery. Additionally, some patients failed to respond to radiation and chemotherapy, so their treatment outcomes and prognosis are quite unsatisfactory, leading to the 5-year relative survival rate of advanced KIRC less than 10% [8][9][10] . It is essential to avoid underestimating the potential future costs of kidney cancer to the global health system and the economy.…”
Section: Introductionmentioning
confidence: 99%